Endomorphin-2 Inhibition of Substance P Signaling within Lamina I of the Spinal Cord Is Impaired in Diabetic Neuropathic Pain Rats - Wan, Fa-Ping; Bai, Yang; Kou, Zhen-Zhen; Zhang, Ting; Li, Hui; Wang, Ya-Yun; Li, Yun-Qing (Frontiers in Molecular Neuroscience, 2017)
Opiate analgesia in the spinal cord is impaired in diabetic neuropathic pain (DNP), but until now the reason is unknown. We hypothesized that it resulted from a decreased inhibition of substance P (SP) signaling within the dorsal horn of the spinal cord. To investigate this possibility, we evaluated the effects of endomorphin-2 (EM2), an endogenous ligand of the μ-opioid receptor (MOR), on SP release within lamina I of the spinal dorsal horn (SDH) in rats with DNP. We established the DNP rat model and compared the analgesic efficacy of EM2 between inflammation pain and DNP rat models. Behavioral results suggested that the analgesic efficacy of EM2 was compromised in the condition of painful diabetic neuropathy. Then, we measured presynaptic SP release induced by different stimulating modalities via neurokinin-1 receptor (NK1R) internalization. Although there was no significant change in basal and evoked SP release between control and DNP rats, immunohistochemistry (IHC) data showed that EM2 failed to inhibit SP release by noxious mechanical and thermal stimuli in DNP but not in control and inflammation pain model. We also observed that EM2 decreased the number of FOS-positive neurons within lamina I of the SDH but did not change the amount of FOS/NK1R double-labeled neurons. Finally, we identified a remarkable decrease in MORs within the primary afferent fibers and dorsal root ganglion neurons by western blot and IHC. Taken together, these data suggest that reduced presynaptic MOR expression might account for the loss of the inhibitory effect of EM2 on SP signaling, which might be one of the neurobiological foundations for opioid inefficacy in the treatment of DNP.